2023
DOI: 10.1021/acsaelm.2c01488
|View full text |Cite
|
Sign up to set email alerts
|

Demonstration of Synaptic Behavior in a Heavy-Metal-Ferromagnetic-Metal-Oxide-Heterostructure-Based Spintronic Device for On-Chip Learning in Crossbar-Array-Based Neural Networks

Abstract: Nanomagnetic and spintronic devices, which make use of physical phenomena in materials and interfaces like perpendicular magnetic anisotropy (PMA) and spin–orbit torque (SOT) to exhibit multiple electrically readable and controllable states, have been widely considered as synaptic elements in analog crossbar arrays for on-chip learning of analog neural networks (ANN). Here, in such a heavy-metal-ferromagnetic-metal-oxide-heterostructure-based (Pt/Co/SiO2) spintronic device, multiple mixed states are first demo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 73 publications
2
19
0
Order By: Relevance
“…Under the assumption that the thickness of the heavy metal layer is higher than the spin diffusion length inside the metal, spin current density is defined as j s = j c × θ SH , where j c is in-plane charge current density and θ SH is the spin Hall angle of the heavy metals. For our simulation of both the devices without defects and with defects, we consider θ SH = 0.1, corresponding to platinum (Pt), which has been used as the heavy metal in the recent experimental demonstrations of such domain-wall synapse by Yadav et al [26]. Yadav et al have, in fact, reported this value of spin Hall angle in Pt in the same report [26] by carrying out hysteresis-loop-shift measurement on their device (following the method described by Hu and Pai [53] and Pai et al [54]).…”
Section: Simulation Methodology and Parameter Valuesmentioning
confidence: 99%
See 3 more Smart Citations
“…Under the assumption that the thickness of the heavy metal layer is higher than the spin diffusion length inside the metal, spin current density is defined as j s = j c × θ SH , where j c is in-plane charge current density and θ SH is the spin Hall angle of the heavy metals. For our simulation of both the devices without defects and with defects, we consider θ SH = 0.1, corresponding to platinum (Pt), which has been used as the heavy metal in the recent experimental demonstrations of such domain-wall synapse by Yadav et al [26]. Yadav et al have, in fact, reported this value of spin Hall angle in Pt in the same report [26] by carrying out hysteresis-loop-shift measurement on their device (following the method described by Hu and Pai [53] and Pai et al [54]).…”
Section: Simulation Methodology and Parameter Valuesmentioning
confidence: 99%
“…For our simulation of both the devices without defects and with defects, we consider θ SH = 0.1, corresponding to platinum (Pt), which has been used as the heavy metal in the recent experimental demonstrations of such domain-wall synapse by Yadav et al [26]. Yadav et al have, in fact, reported this value of spin Hall angle in Pt in the same report [26] by carrying out hysteresis-loop-shift measurement on their device (following the method described by Hu and Pai [53] and Pai et al [54]). Spin diffusion length in Pt has been found to be 3-4 nm [55,56].…”
Section: Simulation Methodology and Parameter Valuesmentioning
confidence: 99%
See 2 more Smart Citations
“…[ 1–6 ] Large anti‐damping SOTs are of utmost interest and play a pivotal role in ultrafast magnetization switching, [ 3,7 ] spintronic oscillators, [ 4,6,8–10 ] as well as the emerging area of spintronic‐based neuromorphic computing. [ 11–15 ] In the FM/HM system, the SOT is generated either via the spin Hall effect [ 16–19 ] from the HM layer and/or the Rashba–Edelstein effect [ 20,21 ] from the interface between the FM and HM layers. In both cases, when a charge current flows in the xnormal-$x\text{-}$direction, it generates a spin current in the znormal-$z\text{-}$direction with the spin polarization along the ynormal-$y\text{-}$direction, which can apply an in‐plane anti‐damping torque on the adjacent FM layer.…”
Section: Introductionmentioning
confidence: 99%